Influence of footwear choice, velocity and surfaces on tibial accelerations experienced by field hockey participants during running - Greenhalgh, A.; Sinclair, J.; Leat, A.; Chockalingam, N. (Footwear Science, 2012)
Field hockey is a physically demanding sport, exposing participants to potential overuse injuries linked to high levels of impact shock. This study evaluated the influence of footwear, surface and running velocity on impact shock in field hockey participants. Nine elite university male field hockey participants (age 21±1.69 years, height 175.75±6.56cm and mass 78.13±12.11kg) volunteered for this study. A skin-mounted accelerometer was used to measure tibial impact shock during forward running at 3.3 and 5.0ms-1 on concrete and a field hockey-specific synthetic sports surface (SSS), in a range of shoes (n=5) typically worn by field hockey participants. A significant effect was found for surface and velocity. No significant differences were found between footwear conditions. The study concluded that reducing running velocity and participating in all field hockey activities on a suitable SSS may reduce the occurrence of injuries linked to impact shock in a field hockey population.